Institutional Management Model of Joint Village-Owned Enterprises (BUMDes) in North Sumatera - Agus Suriadi; Husni Thamrin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to find a BUMDes institutional management model in North Sumatra and find an effective BUMDes management model as an independent and professional rural economic institution. As for the research informants are key informants (key informants), namely those who know and have a variety of basic information needed in research. The key information of this study is that officials in the Village Community Empowerment and Sub-District Head of Sei Rampah and the Village Heads in Sei Rampah District, Serdagang Bedagai District, and the main informants, those who are directly involved in the social interactions under study. This study examines the data that has been obtained in depth by examining all available data from various data sources collected. The results of the study showed that the BUMDes and Sei Rampah institutions developed well over the past 2 years since 2017. This happened because the BUMDes and Sei Rampah together with the management continued to reform in all aspects. Among BUMDes Together doing development in terms of Local Resources that is utilizing the village communities who are members of BUMDes to be involved in the development of BUMDes in the future. While the capacity and experience of the managers of the Joint Bumdes became an important capital for the development of the Joint BUMDes Sei Rampah. Another thing is the development of the BUMDes Institution because of financial support from villages that have included their capital in the Joint BUMDes. The creativity of the Joint BUMDes Management Board in collaborating with various other institutions makes the existence of the Joint BUMDes  increasingly exist in running the wheels of its business.